Customer Intention toward Theme Park: The Mediating Role of Customer Attitude on The Impact of Service Quality and Experiential Marketing - Dwi Efrarin Purnamadita; Dian Tauriana (The Winners, 2012)
Dunia Fantasi (Dufan) located in Taman Impian Jaya Ancol is one leading recreational unit with specific characteristics as a theme park. A research was done towards with service quality and implementation of experiential marketing applied in Dufan using path analysis. Experiential marketing was studied to have a direct effect, positive and significant impact on customer attitude variables. The basic objective of this research is to determine the effect of service quality and implementation of experiential marketing to customer attitude and its impact on customer intention of Dufan. Data collection was conducted through questionnaire given to Dufan visitors. From the results of data analysis we found that service quality has not significantly influenced customer’s attitude. The study revealed that the direct effect between experiential marketing and customer intention is 'strong’. As a subsequent finding, service quality has not given a significant effect on customer intention. However, experiential marketing was found having an indirect influence on customer intention mediated by attitude, in which the results of the study suggested that the indirect effect is 'strong'. Eventually, customer attitude has a direct positive and significant impact on customer intention variables. The direct influence of customer attitude to customer intention in Fantasy World,was 'strong'.